Sporobolomyces agrorum sp. Nov. and sporobolomyces sucorum sp. nov., two novel basidiomycetous yeast species isolated from grape and apple must in italy - Lorenzini, Marilinda (2020)
During a survey of yeast populations associated with grape and apple musts used for wine and cider fermentation, respectively, six pink-coloured ballistoconidia-forming yeasts belonging to the order Sporidiobolales (Basidiomycota) were isolated. Phylogenetic analysis inferred using sequences of the internal transcribed spacer (ITS), the D1/D2 domain of the large subunit rRNA gene, the small subunit (SSU) rRNA gene and DNA-directed RNA polymerase II subunit (RPB2) indicated that the six isolates were separated in two novel species. One of the new species, Sporobolomyces agrorum sp. nov., isolated from grape must, had Sporobolomyces roseus and Sporobolomyces metaroseus as its closest relatives, but showed four/two and 16 nucleotide substitutions in the D1/D2 and ITS regions, respectively, to these two species. The other novel species, Sporobolomyces sucorum sp. nov., was found in apple must and was closely related to Sporobolomyces pararoseus and Sporobolomyces patagonicus, but showed two/three and five substitutions in those two regions for its closest relatives. We detected additional representatives of this species, most of them isolated from grapes whose sequences were already available on public databases. A sexual stage could not be observed for the novel species.